Anticancer and biological properties of leaf and flower extracts of Echinacea purpurea (L.) Moench - Mohamed Sharif, Khawla Omran; Tufekci, Enis Fuat; Ustaoglu, Buket; Altunoglu, Yasemin Celik; Zengin, Gokhan; Llorent-Martínez, E.J.; Guney, Kerim; Baloglu, Mehmet Cengiz (Elsevier BV, 2021)
Abstract Echinacea purpurea (L.) Moench is an important medicinal herb; its roots, leaves and, flowers have been used by the food and pharmaceutical industries. In this study, DNA protection, antimicrobial, antioxidant-enzyme inhibition, and antiproliferative activities of water, methanol (MeOH), and ethyl acetate (EA) extracts of leaves and flowers of E. purpurea were evaluated. In addition, total phenolics and flavonoids, as well as individual compounds, were identified using colorimetric assays and HPLC-ion trap mass spectrometry, respectively. Chicoric acid and its isomer were the most abundant natural compounds, with concentrations similar to previous studies of E. purpurea. All extracts had antimicrobial activity against a broad range of bacteria, particularly Enterococcus faecalis. The antiproliferative activity of the extracts on the HeLa cells was shown. The lowest value of IC50 (73 μg/ml) came from the 24 h MeOH extract of flowers. The water extract of leaves showed strong antioxidant activity with the DPPH, ABTS, CUPRAC, and FRAP assays. EA and MeOH extracts of leaves showed a significant inhibition ability of cholinesterase and tyrosinase, respectively. The presented study suggested that E. purpurea extracts had promising therapeutic properties. Further investigation at the cellular level could be done to highlight the mechanism behind these biological activities.
Keywords: 3. Good health